Efficiency Analysis of Centrifugal Pumps in Raw Water Intake at Station 3 Water 10, PT. Indah Kiat Pulp and Paper, Perawang - Kurniawan, Iwan (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Riau, 2024)
This study aims to analyze the operational efficiency of centrifugal pumps in the Raw Water Intake system at Station 3 Water 10 PT. Indah Kiat Pulp and Paper Perawang. The methodology used includes direct measurement of water discharge parameters, pressure, and electrical power using a flowmeter, pressure gauge, and clamp meter. Efficiency data is calculated using the standard pump efficiency formula. The results show that the actual pump efficiency is below the catalog efficiency, which is 52%, indicating the potential for energy loss or decreased pump performance. This study provides recommendations for maintenance and operational optimization to improve the efficiency of the pumping system. This study is useful for industrial engineering practitioners and facility management in improving energy efficiency.